Pengaruh Insentif Terhadap Profesionalisme Kerja Karyawan di Hotel Truntum Kota Padang - Clara Safitri; Trisna Putra; Arif Adrian (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
The research on the influence of incentives on the work professionalism of Truntum Padang Hotel employees was motivated by the implementation of observations and interviews during industrial field experience at the Truntum Padang Hotel, where several problems were found related to the incentives and work professionalism of Truntum Padang Hotel employees. The purpose of this study was to determine the effect of incentives on employee professionalism at Truntum Hotel in Padang City A quantitative research type with a causal associative approach was chosen in this study. The population is employees at Trumtum Hotel with a sample size of 70 respondents. Primary data were collected using a questionnaire consisting of 29 statements, which had been tested for validity and reliability. The data is described through the level of achievement of respondents and hypothesis testing using simple linear regression analysis techniques. Based on hypothesis testing, it is known that the Adjusted R value is 0.168, indicating the influence of incentives on professionalism of 16.8% and 83.2% is determined by other factors. Furthermore, it is known that the F value is 13,709 with a significance level of 0.000 <0.05, so it can be concluded that incentives (X) have a significant effect on professionalism (Y). The regression coefficient value is 0.829 with a sig value of 0.000 <0.05.